Contextual Support for Less Salient Homophones and Pun Humor Appreciation: Evidence From Eye Movements in Reading Chinese Homophone Puns - Zheng, Wei; Wang, Xiaolu (Frontiers in Psychology, 2022)
Punning is an important means of creating humorous effects by intentionally exploiting semantic ambiguity. Previous psycholinguistic research on puns has mainly focused on the process of meaning retrieval in homograph puns, while it is still not entirely clear how readers dynamically utilize contextual information to understand homophone puns. In the current investigation, 68 native Chinese participants were recruited to read three types of experimental sentences while their eye movements were recorded: (1) the homophone-pun sentences where the less salient homophone was visually presented, (2) the homophone-salient sentences where the salient homophone was used, and (3) the homophone-error sentences where the critical context noun in the homophone puns was replaced with an unrelated word. Humor rating results of the homophone puns and the homophone-salient sentences demonstrated that the less salient homophones rather than the salient ones elicited much larger humor responses when presented visually in the same potential pun context. In addition, the reverse fixation pattern in the homophone area and the spill-over region also suggested that meanings of the salient homophones were more recoverable even when not presented visually. Statistical analyses of the homophone puns and the homophone-error sentences showed that the semantic relatedness between the critical context noun and the less salient homophone could significantly predict the humor rating scores of Chinese readers. Taken together, less salient homophones need to receive more contextual support to balance out the advantages of salient homophones before generating a humorous pun interpretation.